Tattooing or Metallic Clip Placement? A Review of the Outcome Surrounding Preoperative Localization Methods in Minimally Invasive Anterior Resection Performed at a Single Center. Issue 1 (February 2022) - Lin, Chang-Lin; Chen, Chou-Pin; Chiang, Feng-Fan; Chen, Chou-Chen; Chen, Ming-Cheng; Chen, Chih-Tien; Lin, Chun-Yu; Cheng, Hou-Hsuan; Shao, Yen-Chen
Abstract : Background: For minimally invasive colorectal surgery, preoperative localization is a typical procedure. We here aimed to analyze compared 2 different localization methods in terms of short-term outcomes, like the operative outcome and postoperative complication rates based on real-world data. Materials and Methods: This was a retrospective analysis study conducted at a medical center. We enrolled patients who were presented with colonic tumor between January 1, 2016, and December 31, 2019, and they had undergone laparoscopic anterior resection in a single institution. Data included patient characteristics, operative outcome, length of hospital stay, and postoperative complications. Results: The preoperative localization group had a better resection margin (4 vs. 3 cm; P <0.001) and fewer procedures of intraoperative colonoscopy (4.67% vs. 18.22%; P =0.002). Lymph node harvest occurred more in patients with endoscopic tattooing procedures than with metallic clip procedures (25 vs. 20; P =0.031). No significant difference was found regarding postoperative complications and the length of hospital stay. Conclusions: Preoperative localization in a laparoscopic anterior resection led to better surgical planning and resection margin. The metallic clip placement was helpful in the preoperative localization and setting. The endoscopic tattooing method had a larger lymph node harvest and with fewer intraoperative colonoscopy.